Effect of E Samsat Service on Motor Vehicle Tax Revenue at UPT. Regional Revenue Service Operational Support Center - Lubis, Nadratul Hasanah; Harahap, Rahmat Daim (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Vehicle taxes include first-rate or local taxes controlled by the provincial government. Together with the Motor Vehicle Tax Agency, the local government built an office in Samsat. This bureau offers a number of services, one of which is E-Samsat. This study looks at the impact of E-Samsat on Motor Vehicle Tax receipts at UPT. North Sumatra Regional Revenue Service Support Center. The method of analysis uses descriptive quantitative methods. The results showed that E-Samsat had an impact on motor vehicle tax revenues at UPT. North Sumatra Regional Revenue Support Center.